Syphilis Maligna (Lues Maligna): A Case Report - Rosa Giménez-García (Dermatology, 2016)
Syphilis is a sexually transmitted disease (STD) produced by Treponema pallidum, an anaerobic filamentous spirochete, which has a tropism for several organs and tissues in the body. A rare form of detructive syphilide, with deeply ulcerative covered with thick crust lesions was described under the name malignant syphilis (lues maligna).1 Most of the cases, resulting from human immunodeficiency virus (HIV)-induced suppression of cell mediated immunity, have been reported in HIV positive patients1-20 but some cases occur in individuals with poor health, alcoholic or immunocompetent patients